2020
DOI: 10.3390/ijerph17228410
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Particulate Matter 2.5 Induces Epithelial-to-Mesenchymal Transition and Upregulation of SARS-CoV-2 Receptor during Human Pluripotent Stem Cell-Derived Alveolar Organoid Development

Abstract: Growing evidence links prenatal exposure to particulate matter (PM2.5) with reduced lung function and incidence of pulmonary diseases in infancy and childhood. However, the underlying biological mechanisms of how prenatal PM2.5 exposure affects the lungs are incompletely understood, which explains the lack of an ideal in vitro lung development model. Human pluripotent stem cells (hPSCs) have been successfully employed for in vitro developmental toxicity evaluations due to their unique ability to differentiate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
(31 reference statements)
0
32
0
2
Order By: Relevance
“…When PM 2.5 invades the human body, ACE-2, as the receptor for SARS-CoV-2 to enter cells, will protect against renin–angiotensin system-induced lung injuries by cleaving Angiotensin II to limit substrate availability in the adverse AEC-Ang II-Ang II receptor 1 axis ( Parajuli et al, 2014 ). Therefore, PM 2.5 can increase the SARS-CoV-2 susceptibility for human body by enhancing the expression of AEC-2 and its cofactor TMPRSS2 ( Kim et al, 2020 ). An in vivo experimental study has confirmed that the expression level of ACE-2 in the lung of experimental mice was significantly increased after being induced by PM 2.5 ( Lin et al, 2018 ).…”
Section: Influence Of Ambient Aerosols On the Transmission Of Covid-1mentioning
confidence: 99%
“…When PM 2.5 invades the human body, ACE-2, as the receptor for SARS-CoV-2 to enter cells, will protect against renin–angiotensin system-induced lung injuries by cleaving Angiotensin II to limit substrate availability in the adverse AEC-Ang II-Ang II receptor 1 axis ( Parajuli et al, 2014 ). Therefore, PM 2.5 can increase the SARS-CoV-2 susceptibility for human body by enhancing the expression of AEC-2 and its cofactor TMPRSS2 ( Kim et al, 2020 ). An in vivo experimental study has confirmed that the expression level of ACE-2 in the lung of experimental mice was significantly increased after being induced by PM 2.5 ( Lin et al, 2018 ).…”
Section: Influence Of Ambient Aerosols On the Transmission Of Covid-1mentioning
confidence: 99%
“…Diesel fine PM (dPM) 2.5 exposure has been well documented to disturb alveolar epithelial cell differentiation, in parallel with the increased nicotinamide adenine dinucleotide phosphate oxidases expression, as well as inflammation. In response to the dPM2.5 exposure, ACE2 receptor via which SARS-CoV-2 enters the target cells, and the cofactor transmembrane protease serine 2 (TMPRSS2) are highly upregulated in the alveolar epithelial cells ( Kim et al, 2020a , 2020b ). Importantly, generation and emission of DEPs from diesel engines are one of the main components of aerial PM ( Ohtoshi et al, 1998 ).…”
Section: Diesel Exhaust Particles and Sars-cov-2 Infectionmentioning
confidence: 99%
“…1 B). Since the dimensions of SARS-CoV-2 varies between approximately 70–90 nm, it can be carried to many intracellular organelles after entrance to the human’s cells ( Kim et al, 2020a , 2020b ). Following the post-“Stay Home Order” period Northwestern US city, the median traffic intensity and road occupancy declined approximately by one-third to half.…”
Section: Diesel Exhaust Particles and Sars-cov-2 Infectionmentioning
confidence: 99%
“…While public response to particulate matter toxicity, as an obscure risk that mainly has consequences in the long term, may be delayed for some time, recent research indicates that toxic particles in the atmosphere play an essential role in spreading the current COVID-19 pandemic, and that therefore their systematic removal is a high public health priority. Thus, for example, an undeniable and high correlation was found between the concentration of PM2.5 particles in the air, on one hand, and both incidence and mortality from COVID-19, on the other [12][13][14][15]. glo biti samo privremeno rešenje problema.…”
Section: Poštovano Uredništvomentioning
confidence: 99%
“…Iako se javno zdravstveni odgovor na toksičnost čestica, kao nejasan rizik koji uglavnom ima posledice u dužem vremenskom periodu, može odložiti na neko vreme, nedavna istraživanja pokazuju da toksične čestice u atmosferi igraju ključnu ulogu u širenju trenutne pandemije COVID-19 i da stoga njihovo sistematsko uklanjanje predstavlja cilj visokog prioriteta za javno zdravlje. Tako je, na primer, utvrđena nesporna i visoka korelacija između koncentracije čestica PM2,5 u vazduhu, s jedne strane, i incidencije i mortaliteta od COVID-19, s druge strane [12][13][14][15].…”
Section: Poštovano Uredništvounclassified